2018
DOI: 10.3390/antiox7010013
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Mitochondrial Dynamics: The Yin and Yang of Mitochondrial Dysfunction and Cancer Progression

Abstract: Mitochondria are organelles with a highly dynamic ultrastructure maintained by a delicate equilibrium between its fission and fusion rates. Understanding the factors influencing this balance is important as perturbations to mitochondrial dynamics can result in pathological states. As a terminal site of nutrient oxidation for the cell, mitochondrial powerhouses harness energy in the form of ATP in a process driven by the electron transport chain. Contemporaneously, electrons translocated within the electron tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
252
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 365 publications
(282 citation statements)
references
References 228 publications
11
252
0
1
Order By: Relevance
“…Interestingly, further analysis of many key redox genes implicated in other antioxidant systems including SOD family members, the major H 2 O 2 scavenger catalase (CAT), glutathione peroxidase (GPX) family members, glutamate‐cysteine ligase catalytic subunit (GCLC), glutathione synthetase (GSS), NAPDH oxidase (NOXs) family members and dual oxidase1 (DUOX1), indicated that only SOD2 was uniquely upregulated in both high TLR2‐expressing GC cells we studied (Figs. e– g ).…”
Section: Resultsmentioning
confidence: 92%
“…Interestingly, further analysis of many key redox genes implicated in other antioxidant systems including SOD family members, the major H 2 O 2 scavenger catalase (CAT), glutathione peroxidase (GPX) family members, glutamate‐cysteine ligase catalytic subunit (GCLC), glutathione synthetase (GSS), NAPDH oxidase (NOXs) family members and dual oxidase1 (DUOX1), indicated that only SOD2 was uniquely upregulated in both high TLR2‐expressing GC cells we studied (Figs. e– g ).…”
Section: Resultsmentioning
confidence: 92%
“…; Jezek et al. ). Generation of ROS in mitochondria in the diabetic heart is increased by multiple mechanisms (Bugger and Abel ), and OLETF at 25–30 weeks of age show mild diastolic dysfunction with preserved systolic function (Takada et al.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, exposure of endothelial cells to a high concentration of glucose upregulated Fis1 expression and elevated mitochondrial levels of ROS (Shenouda et al 2011). On the other hand, endogenous ROS and exogenous ROS have been shown to induce shortening and fragmentation of mitochondria in cardiac and noncardiac cells (Huang et al 2016;Tsushima et al 2017;Jezek et al 2018). Generation of ROS in mitochondria in the diabetic heart is increased by multiple mechanisms (Bugger and Abel 2010), and OLETF at 25-30 weeks of age show mild diastolic dysfunction with preserved systolic function (Takada et al 2012;Kouzu et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dynamics and ROS production are intrinsically linked. The fragmented mitochondrial phenotype is observed with mitochondrial ROS overproduction (Huang et al, 2016;Jezek, Cooper, & Strich, 2018). Recent studies have shown that blocking or inhibiting Drp1 in ROS-mediated oxidative stress improved mitochondrial function and decreased fragmentation (Gan, Huang, Yu, Yu, & Yan, 2015;Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%